Abnormalities of cerebrospinal fluid amino acids in patients with the Guillain-Barré syndrome. Issue 1 (January 1981) - Corston, R N; McGale, E H; Stonier, C; Aber, G M; Hutchinson, E C
Abstract : Measurements of cerebrospinal fluid (CSF) and plasma amino acid concentrations have been made in 12 patients with the Guillain-Barré syndrome. The CSF protein concentration was normal in seven specimens and raised in 13. Abnormalities of the CSF amino acid profile were found in all specimens but were more marked in those with a raised CSF protein concentration. The possible causes and diagnostic significance of these changes are discussed.